2021
DOI: 10.2320/matertrans.mt-m2020373
|View full text |Cite
|
Sign up to set email alerts
|

Recent Studies on Titanium Refining: 2017–2020

Abstract: Titanium oxide can be converted directly to its metallic state. This extraordinary technology is realized in a CaCl 2 -based molten salt that can extract oxygen ions from the cathode. Several discussions have been exchanged in the field of electrochemistry and metallurgy in the last two decades. Recent papers on titanium refining are overviewed by selecting popular papers, especially those published in this journal, Materials Transactions. Basic and scientific studies on titanium and its refining are briefly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…Readers can find that two special issues related to SEM and TEM analyses were published from Materials Transactions, of which studies were introduced in the CTR. 110,111) For an additional comment, one of the awarded papers dealt with direct reduction of TiO 2 3) and interested readers can find the related topic reviewed extensively in a latest CTR paper by Suzuki et al 112)…”
Section: Editor's Remarksmentioning
confidence: 99%
“…Readers can find that two special issues related to SEM and TEM analyses were published from Materials Transactions, of which studies were introduced in the CTR. 110,111) For an additional comment, one of the awarded papers dealt with direct reduction of TiO 2 3) and interested readers can find the related topic reviewed extensively in a latest CTR paper by Suzuki et al 112)…”
Section: Editor's Remarksmentioning
confidence: 99%
“…Other potential methods are the Fray-Farthing-Chen Cambridge [11], Armstrong [12], Council for Scientific and Industrial Research Ti process [13], direct reduction of titanium slag process [14], and hydrogenassisted magnesiothermic reduction (HAMR) [15]. Moreover, a molten salt method using TiS 2 and TiO 2 via the Ono and Suzuki process led the way to cheaper Ti metal powder production [16][17][18]. It was reported that the recently reported HAMR process could reduce energy consumption to about 62% of the Kroll process [11].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the complex industrial manufacturing process, several researchers have focused on exploring novel processing methods for the production of metallic titanium, and recent researches are summarized by Suzuki et al 2) Some researchers have reported the synthesis of metallic titanium particles employing an electrochemical method, with molten calcium chloride or molten salt as the medium, 36) whereas others have also proposed producing metallic titanium particles through magnesiothermic and calciothermic reductions using molten salts. 7,8) In our previous study, we reported a thermolysis (thermal decomposition) method for the production of titanium ingots.…”
Section: Introductionmentioning
confidence: 99%